The construction of biodiversity as a political and scientific problem - MAUZ, Isabelle; MAUZ, Isabelle (Sciences, Eaux & Territoires, 2011)
How has biodiversity defined itself as a public problem, by what processes has the notion become an important issue in public polices? This text presents a chronology of the phenomenon.